Korelasi CBR Kondisi Soaked Dan Unsoaked Agregat Lapisan Pondasi Bawah (LPB) Pada Timbunan Jalan (Studi Kasus: Agregat LPB Jalan di Pulau Bengkalis) - Junaidi Sipil (Politeknik Negeri Bengkalis, 2022)
By origin, the surface soil on Bengkalis Island is a type of sedimentary soil in which the subgrade has a relatively low carrying capacity and also has a low surface elevation and is prone to water inundation (flooding). In order to increase the bearing capacity and increase the elevation of the road surface, the road construction is filled with aggregate in the sub-base layer (LPB) of the road. All road LPB aggregates used on Bengkalis Island are imported from outside and spread over several quarries. Before the road LPB aggregate is used as a road construction fill material, the LPB aggregate is first tested for CBR carrying capacity under soaked sample conditions. While in the field, to check the quality of the CBR carrying capacity, testing was carried out under unsoaked sample conditions. In this study, uses road LPB aggregates from 3 (three) different quarries. A series of tests were carried out in accordance with SNI, to determine the aggregate property values and determine the correlation between the unsoaked CBR bearing capacity and the soaked CBR of the aggregate. The bearing capacity correlations of unsoaked CBR and soaked CBR are obtained with a strong correlation level (R2 > 80%) with different correlation equations between the aggregates of each query.